Undescended testis: 513 patients' characteristics, age at orchidopexy and patterns of referral. Issue 5 (13th November 2013) - Nah, Shireen A; Yeo, Charleen S W; How, Guo Yuan; Allen, John C; Lakshmi, Narasimhan K; Yap, Te-Lu; Jacobsen, Anette S; Low, Yee; Ong, Caroline C P
Abstract : Objective: Undescended testis (UDT) affects 1–6% of males. Current recommendations are to correct maldescent by 1 year of age. We identify the population characteristics of children referred and managed for UDT, age at referral and orchidopexy, and patterns of referral. Design, setting and patients: Retrospective 5-year review of all patients operated for UDT from 2007 to 2011 in our institution. Patient demographics, neonatal diagnosis of UDT, age at referral, referral source and age at first orchidopexy were recorded. Data are reported as median (range). Results: There were 513 boys with 576 undescended gonads; 450 (88%) had unilateral UDT. Congenital (present at birth) UDT was diagnosed in 287 (56%) children. Seventy-nine (15%) were premature births, 41 (8%) had associated major genitourinary abnormalities. Median age at referral was 1.1 (0–16.2) years; median age at first orchidopexy was 1.6 (0–17.2) years. When corrected for age, those with a history of prematurity and associated major genitourinary malformations were referred and operated on earlier. There was no difference in age at referral and orchidopexy when comparing unilateral versus bilateral maldescent, and palpability of UDT. Of those with congenital UDT, 70% were operated at beyond 1 year of age. Those referred from public tertiary hospitals were younger than those referred from community clinics (p<0.0001) and private healthcare institutions (p=0.003). Conclusions: Despite early diagnosis in many patients with UDT, most are referred and operated after 1 year of age, even in congenital UDT. Premature babies, those with major genitourinary anomalies, and those seen in public tertiary hospitals are referred earlier. Community health initiatives must emphasise prompt referral to allay the impact of delayed surgery.